Perceptions of Community College Students to Flexible Learning Modality: Inputs for Pedagogical Interventions (American Journal of Multidisciplinary Research and Innovation, 2023)
A flexible learning modality was implemented to provide relevant and quality education as educational institutions respond to the COVID-19 pandemic. Thus, the study examined community college students’ perceptions of a flexible learning modality. The study utilized a non-experimental quantitative research design through a validated survey with 211 students from the selected three community colleges. The data were analyzed using frequency distribution, percentage, weighted mean, ANOVA, and multiple regression. Students’ perceptions towards flexible learning modality with regard to their attitude revealed that students were fairly positive with the learning modality and moderately confident with the set-up of flexible learning. In addition, their level of engagement is noticeably high throughout their learning. Comparing the students’ demographic profiles and perceptions implies no significant differences. The level of engagement and their perceptions of flexible learning concerning readiness showed a negative correlation. However, a positive correlation exists between students’ level of engagement and their attitudes toward the said modality. This suggests that students should receive the appropriate instruction and orientation and be prompted to consider their qualities as flexible learners, as well as their abilities in time management, communication, and technical skills, as these abilities are essential for flexible learning modality.